كتاب "التذكرة بأحوال الموتى وأمور الآخرة" للإمام القرطبي: دراسة تعريفية وصفية (The Book “Reminder of The Conditions of Dead And The Affairs of Afterlife” By Imam AL-Qurtubi: An Introductory Descriptive Study) - خالد, عبد الله; أسمادي, أحمد; الخيرآبادي, محمد أبو الليث (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص مما لا شك فيه أنَّ الإمام القرطبي كان من العلماء البارزين المعروفين الصالحين الزاهدين في الدنيا، ودرس على أكثر من 12 أستاذا، وتخرج على يديه عدة تلاميذ، وله أكثر من 10 كتب ما بين مطبوع ومخطوط ومفقود. وأما كتاب "التذكرة" فاشتمل بين طياته على كل الأحوال التي تتعلق بالموتى والقبر نعيمه وعذابه، وما يتعلق بأمور الآخرة من البعث والنشور والنفخ في الصور، وأحوال الجنة والنار، وما يقع في آخر الزمان من الفتن والملاحم، وأشراط الساعة. واستقى المؤلف مواد الكتاب من المصادر في شتى ميادين العلم، خاصة القرآن الكريم، وكتب الحديث وعلومه، وكتب التفسير، وكتب الرقائق، وكتب الشمائل والدلائل، وكتب التاريخ، وكتب التراجم، وكتب المغازي والسير. واحتوى الكتاب على 1417 حديثا مرفوعا، ومن المآخذ عليه كثرة إيراد الأحاديث والأخبار الضعيفة بل الموضوعة، وكثرة الاستشهاد بالإسرائيليات والمنامات. وهو واسع الانتشار بين الخاصة والعامة، وتوصلت الدراسة إلى مدى عناية الإمام القرطبي بجانب الوعظ. الكلمات المفتاحيّة: التذكرة، أحوال، الموتى، الآخرة، القرطبي. Abstract There is no doubt that ImÉm al-QurÏubÊ was among the most famous, well-known, and pious scholars who preferred abstinence from the worldly life. He studied from more than 12 scholars, and produced numerous students. He has more than 10 books to his name from which some are published; some are manuscripts; and some are extinct. The book "Reminder…" comprises issues related to the dead, the grave and its bounties and its punishments, matters related to the afterlife such as the Doomsday, Resurrection, the blowing of the Trumpet, the conditions of the Heaven and the Hell, and events which will take place at the End of Time—trials, bloodshed beside, and Signs of the Hour. Al-QurÏubÊ based the substance of the book on various sources of knowledge especially the Noble Qur’an, Hadith collections, Qur’anic exegeses, works on asceticism, works on the Prophet’s personal biography, works on arguments, history books, biographical dictionaries, works on the Prophet’s expeditions and battles. The book consists of 1417 marfË‘ aÍÉdÊth. But most of the reports are not only weak but also fabricated; and many of the evidences are derived from Judeo-Christian traditions and dreams. The book is widespread both among general people and scholars. This study discovers Imam al-QurÏubÊ’s expertise on preaching. Keywords: Reminder, the Conditions, the Dead, the Afterlife, al-QurÏubÊ.